Assessment of large-scale wind energy potential in the emerging city of Duqm (Oman). (July 2015) - Al-Yahyai, Sultan; Charabi, Yassine
Abstract: Duqm is an emerging port city for both industrial and truism applications. Energizing such city requires carful utilization of all available resources. Due to its geographical location, Duqm can harness the wind energy through developing grid connected wind farm. Therefore, a proper wind energy assessment using high temporal and spatial data is required before any financial investment. This paper investigates the assessment of a large-scale wind energy potential in the emerging city of Duqm (Oman). The initial wind assessment is conducted by the mean of dynamical downscaling Ensemble Numerical Weather Prediction Models. Multi-criteria decision support system was used to analysis the land suitability for wind energy applications. 25 MW wind farm is also simulated using WAsP to estimate the annual energy production and the wake losses.